Parent-Collected Nasal Swab for Severe Acute Respiratory Syndrome Coronavirus 2 Testing in Children. Issue 5 (12th April 2021) - Lodi, Lorenzo; Rubino, Chiara; Moriondo, Maria; Pisano, Laura; Astorino, Valeria; Citera, Francesco; Giovannini, Mattia; Trapani, Sandra; Resti, Massimo; Ricci, Silvia; Indolfi, Giuseppe; Azzari, Chiara
Abstract : Supplemental Digital Content is available in the text. Abstract : This cross-sectional study, including children hospitalized for severe acute respiratory syndrome coronavirus 2 infection, demonstrates for the first time that nonhealthcare worker parents perform similarly to healthcare workers in the administration to their children of an unsupervised nasal swab for severe acute respiratory syndrome coronavirus 2 detection by following written instructions and video tutorials.